Boosting Specific Energy and Power of Carbon-Ionic Liquid Supercapacitors by Engineering Carbon Pore Structures - Zhang, Dong; Gao, Hongquan; Hua, Guomin; Zhou, Haitao; Wu, Jianchun; Zhu, Bowei; Liu, Chao; Yang, Jianhong; Chen, De (Frontiers in Chemistry, 2020)
Carbon-ionic liquid (C-IL) supercapacitors (SCs) promise to provide high capacitance and high operating voltage, and thus high specific energy. It is still highly demanding to enhance the capacitance in order to achieve high power and energy density. We synthesized a high-pore-volume and specific-surface-area activated carbon material with a slit mesoporous structure by two-step processes of carbonization and the activation from polypyrrole. The novel slit-pore-structured carbon materials provide a specific capacity of 310 F g−1 at 0.5 A g−1 for C-IL SCs, which is among one of the highest recorded specific capacitances. The slit mesoporous activated carbons have a maximum ion volume utilization of 74%, which effectively enhances ion storage, and a better interaction with ions in ionic liquid electrolyte, thus providing superior capacitance. We believe that this work provides a new strategy of engineering pore structure to enhance specific capacitance and rate performance of C-IL SCs.